Relationship between intestinal microbiota and thyroid homeostasis - Fabian-Danielewska, Anna; Stecko, Monika; Wawryków, Agata; Żukowska, Magdalena; Korabiusz, Katarzyna (Journal of Education, Health and Sport, 2019)
The human digestive tract is inhabited by hundreds of bacterial species, both aerobic and anaerobic, bacteriophages, viruses and fungi that collectively are referred to as intestinal microbiota. Microbiota has a significant impact on the production and maintenance of immunological, hormonal and metabolic homeostasis. Dysbiosis is present in inflammations, e.g. intestinal inflammation, autoimmune diseases, e.g. multiple sclerosis, type 1 diabetes, rheumatic diseases, metabolic disorders such as obesity or type 2 diabetes, and mental illness. Currently, numerous studies are underway on the effect of microbiota on thyroid autoimmune diseases. . It seems, that microbiota has a small, if any, effect on the metabolism of iodine and selenium - elements particularly responsible for thyroid homeostasis. However, the relationship between thyroid function and the gastrointestinal tract has been proven.